THE EFFECTIVENES OF REHABILITATION UNINHABITABLE HOUSE PROGRAM SERVICE IN BREBES REGENCY - Nafisa, Rizki; Soesilowati, Etty (Efficient: Indonesian Journal of Development Economics, 2020)
This research are to know the purpose of implementation of the service distribution mechanism and the effectiveness of the distribution the rehabilitation of unhabitable house service program in Brebes Regency. This research is a quantitative research uses two roomates source of the data, ie primary and secondary of data and collected through observation, interview, questionnaire and documentation. The samples of the research were 100 respondens of Reviews These service roomates program spreadedin Brebes district, district and Wanasari Bulakamba distric. The collection of data was Analyzed using descriptive approach. The result of the research Showed that there were five steps of the distribution mecahnism of the service based on the Central Java Governor Regulation Number 48 Year 2017 as follows planning, funding, implementing, monitoring, evaluating and reporting. Based on the Data analysys of the accuracy of purpose variables Showed the uneffectiveness of result in aiming the purpose of presentation with the number 55.94%. Satisfaction variable towards the program Showed the unsatisfaction towards the program with the number of presentations 57.84%, and the target of variable accuracy Showed that the targets of the program have been accomplished with the number of presentations 84.07%. The suggestion about the research are the need of the guidance towards the receiver of the service on the proposal making, the optimalisation work of the executant of the program, control and Evaluate in order to be fixed and implemented a based on the guidelines provide so that the purpose of the program can be a accomplished.   Tujuan penelitian ini adalah untuk mengetahui implementasi penyaluran dan efektivitas program bantuan rehabilitasi rumah tidak layak huni sumber pendanaan APBD 1 tahun 2018 di Kabupaten Brebes. Penelitian ini menggunakan metode deskriptif kuantitatif. Populasi penelitian ini adalah seluruh penerima bantuan rehabilitasi rumah tidak layak huni sumber pendanaan APBD 1 dengan sampel sebanyak 100 responden melalui teknik pengambilan sampel yaitu purposive sampling. Analisis data menggunakan deskriptif persentase.  Hasil penelitian menunjukan variabel ketepatan tujuan tidak mencapai tujuan dengan nilai persentase sebesar  55,94%, variabel kepuasan terhadap program diperoleh hasil tidak puas terhadap program dengan persentase sebesar 57,84 dan variabel ketepatan sasaran diperoleh hasil sasaran sangat tepat dengan nilai persentase sebesar 84,07%. Saran terkait penelitian ini adalah perlunya pendampingan terhadap penerima bantuan mengenai pembuatan proposal, pengoptimalan kinerja oleh penyelenggara program, serta melakukanpengawasan dan evaluasi agar segera dibenahi dan dijalankan berdasarkan pedoman yang sudah ada sehingga tujuan progran dan sasaran program dapat tercapai.